Efeitos da construção de uma barragem sobre a densidade do ictioplâncton no Rio Verde, Mato Grosso do Sul, Brasil - Reis, Antonio Nogueira dos (2014)
This study aimed to investigate whether during the construction of a dam for hydroelectric there was some negative influence on the reproductive activity of the species of fish, above and below the dam , having as object the density of fish eggs and larvae. Samples were collected monthly on two reproductive periods in nine collection points, grouped into six regions (distant tributaries, tributary near, far upstream, upstream near, downstream near and far, from the dam), through horizontal surface tows, for 10 minutes at dusk , with a plankton net of 0.5 mm mesh. The collections resulted in the capture of 7.524 icthyoplanktonic organisms. Larvae were composed by 14 taxonomic groups. The taxa identified were divided into five orders and Characiformes and Siluriformes showed the highest number of taxa. The two-way ANOVA indicated no interactive effects between regions (F (2, 22) = 4,833; p = 0,018), However, showed significant differences between them, indicating higher occurrence of eggs and larvae of fish downstream of the dam. For the near and distant places of the dam, were also not observed interactive effects, although the main effect for distance from the dam was significant (F (1, 34) = 8,80; p = 0,005), and the mean abundance recorded near the dam was lower than that observed in more distant locations. In front of the results we should conclude that de dam has negatively influenced de fish reproduction near de barrier.